Complement factor B is essential for the proper function of the peripheral auditory system - Brown, LaShardai N.; Barth, Jeremy L.; Jafri, Shabih; Rumschlag, Jeffrey A.; Jenkins, Tyreek R.; Atkinson, Carl; Lang, Hainan (Frontiers in Neurology, 2023)
Sensorineural hearing loss is associated with dysfunction of cochlear cells. Although immune cells play a critical role in maintaining the inner ear microenvironment, the precise immune-related molecular mechanisms underlying the pathophysiology of hearing loss remain unclear. The complement cascade contributes to the regulation of immune cell activity. Additionally, activation of the complement cascade can lead to the cellular opsonization of cells and pathogens, resulting in their engulfment and elimination by phagocytes. Complement factor B (fB) is an essential activator protein in the alternative complement pathway, and variations in the fB gene are associated with age-related macular degeneration. Here we show that mice of both sexes deficient in fB functional alleles (fB−/−) demonstrate progressive hearing impairment. Transcriptomic analysis of auditory nerves from adult mice detected 706 genes that were significantly differentially expressed between fB−/− and wild-type control animals, including genes related to the extracellular matrix and neural development processes. Additionally, a subset of differentially expressed genes was related to myelin function and neural crest development. Histological and immunohistochemical investigations revealed pathological alterations in auditory nerve myelin sheathes of fB−/− mice. Pathological alterations were also seen in the stria vascularis of the cochlear lateral wall in these mice. Our results implicate fB as an integral regulator of myelin maintenance and stria vascularis integrity, underscoring the importance of understanding the involvement of immune signaling pathways in sensorineural hearing loss.